PENANGGULANGAN MASALAH KESEJAHTERAAN SOSIAL OLEH TENAGA KESEJAHTERAAN SOSIAL KECAMATAN (TKSK) (Studi di Kecamatan Karawang Barat Kabupaten Karawang) - Syifa H. Putri Maharani; Kusrin; Maulana Rifa (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
This research departs from a Social Welfare problem in West Karawang District. The high poverty rate and being in the top three of the highest poverty rates in Karawang Regency raises the question of why West Karawang District, which is in the city center, has the highest poverty rate. This research uses descriptive qualitative method. Data collection techniques were carried out by observation, interviews and documentation. The data were taken from selected sources based on purposive sampling technique. This study uses the Budiani effectiveness theory, namely: program target accuracy, program socialization, program objectives, program monitoring. The results of this study indicate that there are many factors that make West Karawang Subdistrict have a high poverty rate, TKSK has been maximized and has streamlined its time and performance for West Karawang District, but there are several other factors that increase the poverty rate, namely urbanization, low education, competitiveness, population density, and availability of jobs. Karawang Regency, especially the social services and government apparatus of West Karawang District, have synergized with TKSK to alleviate social welfare problems in West Karawang District by making existing programs effective to help the community.